Design of a solar energy system for home use in Singapore - Lam, Zhen Yu (2017)
In this project, a typical Grid-tied Solar System and Off-Grid Solar System are analyzed and components included for the implementation of the two systems will be explained in details to provide a better understanding of how the entire Solar Energy System operates.